Patients’ Understanding of Health Information in Online Medical Records and Patient Portals: Analysis of the 2022 Health Information National Trends Survey - Andreadis, Katerina; Buderer, Nancy; Langford, Aisha Tene (Journal of medical Internet research, 2025)
The 21st Century Cures Act mandated instant digital access for patients to see their test results and clinical notes (eg, via patient portals). Entirely using and understanding such health information requires some degree of personal health literacy. This study aims to assess the associations between ease of understanding online health information and various factors, including sociodemographics, health-related variables, numeracy, and technology-related factors. This cross-sectional study used data from the National Cancer Institute's 2022 Health Information National Trends Survey (HINTS), a nationally representative survey of US adults that tracks individuals' access and use of their health information. Data was collected from March to December 2022. The survey was conducted across various US settings using a stratified multistage sampling technique to ensure national representation. Our analysis included 3016 respondents with data for all variables of interest. We conducted bivariate and multivariate analyses to assess the odds of finding health information in online medical records or patient portals as "very easy" to understand compared with "not very easy." In the multivariate analysis, age group (with the 35-49 years group being 1.9 times more likely compared to the ≥75 years group; P=.03), female birth sex (1.4 times more likely; P=.04), ease of understanding medical statistics (8.5 times more likely for those finding it "very easy"; P<.001), patient-provider communication score (increase of 1.1 odds per 1 unit increase; P<.001), and mode of accessing online records (1.8 times more likely via an app and 1.4 times more likely via both an app and website, P=.01 and P=.003, respectively, versus using a website alone) were significant predictors for finding health information "very easy" to understand. Sociodemographic factors, numeracy, patient-provider communication, and method of accessing online records were associated with ease of understanding health information in online medical records or patient portals. Findings from this study may inform interventions to make patient portals and online medical records more patient-centered and easier to navigate.